Crater formation on the surface of refractory alloys during high-power ion-beam processing; Surface and Coatings Technology; Vol. 201, iss. 19-20 (spec. iss.) - Shulov V. A.; Novikov A. S.; Paikin A. G.; Belov A. B.; Lvov A. F.; Remnev G. E. Gennady Efimovich (2007, 2007)
Title screen